2011
DOI: 10.1007/s00134-010-2116-x
|View full text |Cite
|
Sign up to set email alerts
|

Intervention to reduce catheter-related bloodstream infections in a pediatric intensive care unit

Abstract: PN and IT were independent CR-BSI risk factors during the first period. An intervention focused on PN and IT reduction resulted in a sustained decrease of CR-BSI rates in our PICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 44 publications
1
27
0
3
Order By: Relevance
“…Bu oranın NHSN (National Healthcare Safety Network) 2010 verilerinden yüksek (her 1000 kateter gününe 1,9) ancak INICC (International Nosocomial Infection Control Consortium) 2012 verilerinden düşük (her 1000 kateter gününe 10,7) olduğu gözlendi (22,23). Literatürde pediatrik ve erişkin yoğun bakım ünitelerinde her 1000 kateter günü için 1,6-60 aralığında kateter ilişkili kan akımı enfeksiyon oranları bildirilmiştir (14,(24)(25)(26)(27)(28)(29).…”
Section: Discussionunclassified
“…Bu oranın NHSN (National Healthcare Safety Network) 2010 verilerinden yüksek (her 1000 kateter gününe 1,9) ancak INICC (International Nosocomial Infection Control Consortium) 2012 verilerinden düşük (her 1000 kateter gününe 10,7) olduğu gözlendi (22,23). Literatürde pediatrik ve erişkin yoğun bakım ünitelerinde her 1000 kateter günü için 1,6-60 aralığında kateter ilişkili kan akımı enfeksiyon oranları bildirilmiştir (14,(24)(25)(26)(27)(28)(29).…”
Section: Discussionunclassified
“…In another US study of a planned series of interventions, Bhutta et al [9] saw no change after introducing maximal barrier methods for CVC insertion, but a step reduction in CA-BSI when antibiotic-impregnated CVCs were introduced. Further evidence for the importance of reducing risk factors throughout the duration of CVC in children, not just at insertion, is reported in this issue of Intensive Care Medicine by Rey et al [12] They found that the CR-BSI rate fell from 12/1,000 CVC days to 3/1,000, after they halved the proportion of children receiving total parenteral nutrition and reduced the duration of CVC insertion by 20%.…”
mentioning
confidence: 88%
“…For the same reason, CVCs are more precious in children than in adults and less likely to be replaced unless blocked or clearly infected. Fifth, children are more likely than adults to receive total parenteral nutrition, which increases the risk of CA-BSI [12][13][14]17].…”
mentioning
confidence: 99%
“…4 Thus, although the use of CVC is necessary for the care safe for the neonate who needs intensive care, also predisposes the patient to innumerable complications, and infection is one of the most important events. [5][6] Infections resulting from the use of central catheters can be defined as primary bloodstream infections associated with central venous catheter or infections related to central venous catheter. 5 The first situation is due to consequences of severe systemic infection, bacteremia or sepsis, with no primary focus identified.…”
Section: -3mentioning
confidence: 99%
“…[5][6] Infections resulting from the use of central catheters can be defined as primary bloodstream infections associated with central venous catheter or infections related to central venous catheter. 5 The first situation is due to consequences of severe systemic infection, bacteremia or sepsis, with no primary focus identified. Central venous catheter-related infections occur at the catheter insertion site, without systemic repercussions.…”
Section: -3mentioning
confidence: 99%